Zone-specific reference ranges of fetal adrenal artery Doppler indices: a longitudinal study - Ran Xu; Ziling Zhu; Wenjuan Tang; Qichang Zhou; Shi Zeng (BMC, 2020)
Abstract Background The fetal adrenal gland is a highly vascularized organs and develops two recognizable distinct zones in uetro, inner fetal zone (FZ) and outer definitive zone (DZ). Based on the region supplied, middle adrenal artery (MAA) mainly contribute to FZ while inferior adrenal artery (IAA) mainly to the inferior part of DZ. The purpose of this study was to establish reference ranges of adrenal artery Doppler indices of IAA and MAA, and assess zonal difference of blood supply to fetal adrenal gland. Methods The pulsatility index (PI), resistance index (RI), and systolic:diastolic ratio (S/D) of the IAA and MAA were obtained serially at 4-week intervals in normal fetuses. The MAA and IAA were referred based on the course and location in the gland: IAA referring the artery that mainly branches from the renal artery and walks along the renal upper pole, distributing the inferoposterior part of DZ in the adrenal gland while MAA as arterial blood flowing along the single central adrenal vein in the medial part of the gland. Multilevel modeling was performed to establish the gestational age-associated reference ranges for IAA and MAA. Differences in Doppler indices between the IAA and MAA were assessed. Results One hundred sixty-eight fetuses with 843 observations were included. The IAA had a higher detection rate than the MAA (100% vs 89.2%, p < 0.05). The resistance of IAA had a reduction around 35 weeks of gestation and that of MAA remained unchanged throughout the second half of pregnancy. Lower PI, RI and S/D were observed in the MAA than in the IAA (p < 0.05) from 752 paired measurements. Conclusion There is a zonal difference in blood supply in favor of the fetal zone, which may correspond to its unique function. Reference ranges of Doppler parameters in adrenal artery maybe beneficial for further evaluation of fetal hemodynamics.